There are second in one minute is a sixty second in one minute .

*- Answered by yash chaurasia* On 25 June 2022:11:24:05 AM

**Question 1.** **Asked on :**09 June 2022:04:55:46 PM

How many consonants are there in the English alphabet?

*-Added by Master Purushottam* **General Knowledge** » **Gk **

**Question 2.** **Asked on :**09 June 2022:04:54:49 PM

How many seconds make one hours?

*-Added by Master Purushottam* **General Knowledge** » **Gk**

**Question 3.** **Asked on :**09 June 2022:04:54:26 PM

How many seconds are there in a minute?

*-Added by Master Purushottam* **General Knowledge** » **Gk**

**Answer:**

There are second in one minute is a sixty second in one minute .

*- Answered by yash chaurasia* On 25 June 2022:11:24:05 AM

**Question 4.** **Asked on :**09 June 2022:04:53:59 PM

How many minutes are there in an hour?

*-Added by Master Purushottam* **General Knowledge** » **Gk**

**Question 5.** **Asked on :**09 June 2022:04:53:26 PM

How many days are there in a year?

*-Added by Master Purushottam* **General Knowledge** » **Gk**

**Question 6.** **Asked on :**09 June 2022:04:52:37 PM

Rainbow consist of how many colours?

*-Added by Master Purushottam* **General Knowledge** » **Gk,**

**Question 7.** **Asked on :**09 June 2022:04:51:58 PM

The baby frog is known as...

*-Added by Master Purushottam* **General Knowledge** » **Gk,**

**Question 8.** **Asked on :**09 June 2022:11:09:09 AM

If the 1st term of a series is 7 and 13th term is 35. find the sum of 13 terms of the sequence.

*-Added by Master Purushottam* **Mathematics** » **Arithmetic Progressions **

**Answer:**

a= 7 , a_{13} = 35 _{ }

S_{n} = n2 (a + l)

S_{13} = 132 (7+35)

= 132 x 42

= 13 x 21

= 273

Hence, the sum of the first 13 term of the sequence is 273.

*- Answered by Master Purushottam* On 09 June 2022:11:19:25 AM

**Question 9.** **Asked on :**09 June 2022:10:56:24 AM

Value of the roots of the quadratic equation,

x^{2 }-x-+=0 are.................

*-Added by Master Purushottam* **Mathematics** » **Quadratic Equations**

**Answer:**

CORRECT EQUALTION

x^{2 }-x- 2 =0

=> x^{2 } - x - 6 =0

=> x^{2 }-3x + 2x - 6 =0

=> x(x-3) + 2(x-3) = 0

=> (x - 3) (x+2) = 0

=> x = 3 , x = -2

*- Answered by Master Purushottam* On 09 June 2022:10:57:52 AM

**Question 10.** **Asked on :**09 June 2022:10:42:27 AM

solve for x (in term of a and b):

a/x-b + b/x-a = 2, x≠ a,b

*-Added by Master Purushottam* **Mathematics** » **Algebra Expression**

**Answer:**

a(x-a) + b(x-b)

(x-b) (x-a) = 2

cross multiplying both the sides

a(x-a) + b(x-b) = 2[x^{2}-(a+b)x+ ab]

ax- a^{2 }+ bx -b^{2}_{ }= 2x^{2} -2(a+b)x + 2ab

2x^{2} -3(a+b)x + (a+b)^{2} = 0

2x^{2} -2(a+b)x -(a+b)x + (a+b)^{2} = 0

[2x- (a+b) ] [x-(a+b)] = 0

^{ }_{ }^{ } _{ }^{ }

x = a + b, a + b2

*- Answered by Master Purushottam* On 09 June 2022:10:46:59 AM

User Earned Point: Select

Sponsers link